Penerapan Metode Musyawarah dalam Pembelajaran Kitab-Kitab Turats pada Kelas Al-'Ali di Pondok Pesantren Al-Bidayah Jember - Priyono, Dwi Juli; Azisi, Azisi; Nasrudin, Ahmad (Al-Kafaah : Journal of Arabic Language and Linguistics Education (ALLE), 2024)
This research aims to find out how the consultation method is applied and problems in teaching heritage books in senior classes at the Al-Bidayah Islamic Institute, Jember. This research method is field research, case study. The data sources are the director of the institution, students and teachers of the Al-Bidaya Jember Islamic Institute. Data collection methods include observation, interviews and documentary methods. To ensure the validity of the data, researchers used triangulation techniques. The results of this research are 1) Applying the deliberation method in teaching traditional books using the book Fath al-Mu'in. 2) There are four problems in teaching traditional books using the consultation method. The semester arrangement is lacking with supervision by teachers and institutional leaders, the material presented is difficult according to some students, the activity time starts at half past nine, and the educational method lacks strong sound reinforcement.